Performance and Growth Curve Prediction of Crossbred Chickens from Crossing between Local Roosters and Layer Hens - Akhmad Dakhlan; Rudy Sutrisna; Purnama Edy Santosa (Indonesian Center for Animal Research and Development (ICARD), 2023)
Demand for crossbred chicken (Indonesian native chicken x laying hens) continues to increase. This study aimed to find the best-crossbred chicken resulting from crossing between local/native roosters and laying hens which produce the highest body weight up to eight weeks of age, and its growth prediction using the Gompertz function. Eighteen (18) native roosters (9 Bangkok roosters, 9 Pelung roosters) and 36 laying hens of strains Isa brown, Lohman brown, and Hyline brown (12 each) were used in this study to produce 360 crossbred chickens. Factorial 2x3 (two male local roosters versus three strains of laying hens) using a completely randomized design with 3 replications was applied in this study. The results showed an interaction between native roosters and layer hens on the body weight of crossbred chickens at eight weeks of age. Crossbred chicken from crossing between Pelung rooster and Isa brown layer hen was the best in body weight at eight weeks of age. This crossbred chicken would reach a mature weight of 3026.89 g with an inflection weight of 1113.53 g and an inflection age of 7.40 weeks. In conclusion, crossbred chicken from crossing between Pelung roosters and layer hens of Isa brown strain was the best crossbred with the highest body weight at eight weeks of age. This crossbred chicken could be an alternative for fulfilling the demand for local chicken in Indonesia because the slaughter age could be shortened from 8 months to 8 weeks.